HUBUNGAN PEMANFAATAN BUKU KESEHATAN IBU DAN ANAK (KIA) DENGAN KUNJUNGAN ANTENATAL CARE (ANC) PADA IBU HAMIL DI KLINIK UTAMA PANASEA LUMAJANG - Devi Yustiana; Homsiatur Rohmatin; Farianingsih Farianingsih (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Antenatal care plays an important role in providing quality care because antenatal care contains components of health, screening, disease diagnosis and prevention. The use of the MCH Handbook for pregnant women is one of the strategies so that mothers care about their pregnancy, including during ANC visits. The research objective was to determine the correlation between the use of the MCH handbook and ANC visits at the Main Panesa Lumajang clinic. This research is a type of correlation analysis research that examines the relationship between variables using a cross-sectional approach. The number of samples is 30 respondents. The test used is Fisher’s Exact Test. Among pregnant women who used the MCH handbook, 22 (73.3%) of them regularly performed ANC, and 1 person (3.4%) of whom did not regularly perform ANC. Of the pregnant women who did not use the MCH handbook, there were no pregnant women who regularly performed ANC, and 7 (23.3%) of them did not regularly perform ANC regularly. The results of the analysis using SPSS obtained the value of p = 0,000 < α = 0.05. The conclusion of the results of this study is that there is a relationship between the use of the KIA handbook and ANC visits to pregnant women at the Main Clinic of Panasea Lumajang. The use of MCH and ANC books is very important to support the health and safety of pregnant women and babies.